Coastlines, Coastal Cities, and Climate Change: A Perspective on Urgent Research Needs in the United States - Sandifer, Paul A.; Scott, Geoffrey I. (Frontiers in Marine Science, 2021)
This paper builds upon Friedman et al. (2020) and other reviews and statements but provides an explicit focus on research needed to improve the resilience and survivability of coastal communities as they face existential threats from climate change. It does not attempt a prescriptive analysis of potential research emphases, but instead recommends some key research areas that we believe will help provide a solid foundation for community adaptation. Our perspective is based on our experiences over a combined nearly 95 years of work in research, management, and policy, much of it related to coastal environments and their communities, rather than expert deliberation within a large group or a systematic review. We present a list of 25 research priorities binned into 12 categories and targeted to leaders of coastal communities, interested researchers, funders, students, and the public. These priorities are intended to help start more discussion of research needs with and within communities, and help focus attention of researchers on actions that have potential to identify critical decision points and make positive differences for communities. We conclude that priority research should be undertaken with urgency and a much greater level of trans- and interdisciplinarity and community-participatory approaches than yet seen.